Dating of zircon and monazite from diamondiferous quartzofeldspathic rocks of the Saxonian Erzgebirge - hints at burial and exhumation velocities. - Massonne, H.; Kennedy, Allen; Nasdala, L.; Theye, T. (The Mineralogical Society, 2007)
In order to better understand the formation and evolution processes of ultrahigh pressure (UHP) felsic rocks, we determined the ages of various domains of zircon and monazite crystals from the diamondiferous quartzofeldspathic rocks of the Saxonian Erzgebirge. According to cathodoluminescence imagery and Th/U ratios, three zircon zones were distinguished. Each was dated using several spot analyses from a sensitive high-resolution ion microprobe (SHRIMP) analysing Pb, U and Th isotopes. The results were: (1) core zone - 21 analyses: Th/U less/equal 0.023 and 337.0 plus/minus 2.7 Ma (2 sigma, combined 206Pb/238U-207Pb/235U age); (2) diamond-bearing intermediate zone - 23 analyses: Th/U greater/equal 0.037 and 336.8 plus/minus 2.8 Ma; and (3) rim zone-12 analyses: Th/U = 0.0150.038 (plus one analysis of 0.164) and 330.2 plus/minus 5.8 Ma. The U-Pb obtained ages are virtually concordant. Furthermore, two oscillatory zoned zircon cores (Th/U greater/equal to 0.8) yielded (~concordant) ages of ~400 Ma. Six SHRIMP analyses of monazites gave an age of 332.4 plus/minus 2.1 Ma. In addition, Pb, Th and U contents in monazite were analysed with an electron microprobe (EMP). A mean age of 324.7 plus/minus 8.0 (2σ) Ma was acquired from 113 analyses.By combining the defined ages with previously published P-T conditions, minimum velocities for burial and exhumation were estimated. In addition, we present a likely geodynamic scenario involving age data from the literature as well as this study: beginning 340 million years ago, gneisses at the base of a thickened continental crust (~1.8 GPa, 650C) were transported to depths of at least 130 km, possibly as deep as 250 km. Here they were heated (>1050C) and partially melted and as a result began to rise rapidly. The burial and subsequent ascent back to a depth of 50 km, where zircon rims and monazite formed, took only a few million years and perhaps significantly less.